1998
DOI: 10.1038/bjc.1998.453
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer risk in relation to Helicobacter pylori infection and subtypes of intestinal metaplasia

Abstract: (Correa. 1992). In sequential changes from superficial gastritis to dysplasia and cancer. intestinal metaplasia (TM) plays a pivotal role. This is testified by a high frequency of IM in patients with GC and in their relatives. a similar topographic distribution of IM and GC. and a high IM occurrence in endemic areas with a high risk of GC (Dobrilla et al. 1994). Although most investigators agree with Stemmermann ( 1994) that the risk of GC is proportional to the extent of IM and although IM has been intensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…In gastric cancer, we found no association between the MT content and any clinicopathological parameter. However, our observation that MT is strongly expressed by foci of intestinal metaplasia, which have increased neoplastic potential42, indicates that MT might play a role in the growth and differentiation even of cells within normal‐appearing gastric mucosa. Similarly, although Monden et al 26.…”
Section: Discussionmentioning
confidence: 82%
“…In gastric cancer, we found no association between the MT content and any clinicopathological parameter. However, our observation that MT is strongly expressed by foci of intestinal metaplasia, which have increased neoplastic potential42, indicates that MT might play a role in the growth and differentiation even of cells within normal‐appearing gastric mucosa. Similarly, although Monden et al 26.…”
Section: Discussionmentioning
confidence: 82%
“…The stage of chronic gastritis is related to both its duration and to the host's response to the etiological agent(s) and may have implications for the prognosis and management of the patient. Some studies suggested that the histochemical phenotype of IM is associated with a cancer risk increasing progressively from type I to type III [43,44]. Because a greater extension of metaplasia is associated with a greater proportion of type III IM [40], we uphold the recommendation of the Updated Sydney System discouraging the use of histochemical phenotyping to determine the type of metaplasia.…”
Section: Generating a Clinically Helpful Histology Reportmentioning
confidence: 90%
“…Interestingly, it is the latter type that harbours most genetic changes17 18 and the only IM phenotype that carries a higher risk for gastric cancer 19…”
Section: The Nature Of Intestinal Metaplasiamentioning
confidence: 99%